A Translation Shift Of Simple Sentence Found In The Old Man And The Sea Into Lelaki Tua Dan Laut - Aprilia, Yohana, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S. Pd, M. Hum (2014)
This research studies the simple sentences in The Old Man and the Sea into Lelaki Tua dan Laut novel. The objectives of this research are to classify the variations of shift of simple sentences translation found in The Old Man and the Sea into Lelaki Tua dan Laut, and to describe the translation equivalence of simple sentences found in The Old Man and the Sea into Lelaki Tua dan Laut. This research is a descriptive qualitative research. The data are simple sentences and their translation found in The Old Man and the Sea into Lelaki Tua dan Laut. The data source are novels, the title of the novel are The Old Man and the Sea by Ernest Hemmingway and Lelaki Tua dan Laut by Sapardi Djoko Damono. The data are analyzed by comparing between source language and target language, analyzing based on shift, analyzing based on equivalence, and drawing conclusion. The result of the research show that there are 366 data which contain 16 change variations of simple sentence. The researcher finds 13 variations belong to structure shift. They are: (1) nominal sentence includes (a) nominal sentence (NS) which is translated into adjectival sentence (Adj.S) are 5 data or 1,37%, (b) nominal sentence (NS) which is translated into verbal sentence (VS) are 7 data or 1,91%, (c) nominal sentence (NS) which is translated into nominal sentence (NS) are 44 or 12,02%, (2) verbal sentence includes (a) verbal sentence (VS) which is translated into adjectival sentence (Adj.S) are 9 or 2,46%, (b) verbal sentence (VS) which is translated into nominal sentence (NS) are 8 or 2,19%, (3) prepositional sentence includes (a) prepositional sentence (Prep.S) which is translated into nominal sentence (NS) is 1 datum or 0,27%, (c) prepositional sentence (Prep.S) which is translated into prepositional sentence (Prep.S) are 9 data or 2,46%, (4) passive sentence includes (a) passive sentence which is translated into active sentence is 1 datum or 0,27%, (b) passive sentence which is translated into passive sentence are 1 data or 0,27%, (5) active sentence includes (a) active sentence which is translated into passive sentence are 9 data or 2,46%, (b) active sentence which is translated into active sentence are 209 data or 57,10%, (6) adjectival sentence includes (a) adjectival sentence (Adj.S) which is translated into adjectival sentence (Adj.S) 48 data or 13,11%, (b) adjectival sentence (Adj.S) which is translated into verbal sentence (VS) are 5 data or 1,37%. Also, the researcher finds 2 variations belong to level shift. They are: (1) simple sentence which is translated into noun phrase are 3 data or 0,82%, and (2) simple sentence which is translated into word is 1 datum or 0,27%. Besides structure shift and level shift, the researcher finds simple sentence that is not translated are 6 data or 1,64%. The equivalent of traslation variation of simple sentence can be divided into two, equivalent translation and non-equivalent translation. From 366 data, there are 150 data or 40,98% that belong to equivalent translation and 216 data or 59,02% that belong to non-equivalent translation. So, the translation is dominated by non-equivalent translation.